Loneliness, Living Alone, and All-Cause Mortality: The Role of Emotional and Social Loneliness in the Elderly During 19 Years of Follow-Up. Issue 6 (July 2019) - O'Súilleabháin, Páraic S.; Gallagher, Stephen; Steptoe, Andrew
ABSTRACT: Objective: The aims of the study were to examine the predictive value of social and emotional loneliness for all-cause mortality in the oldest-old who do and do not live alone and to test whether these varied by functional status and personality. Methods: Participants were 413 older adults from the Berlin Aging Study (M [SD] = 84.53 [8.61] years of age) who either lived alone ( n = 253) or did not live alone ( n = 160). Significance values for hazard ratios are reported having adjusted for age, sex, education, income, marital status, depressive illness, and both social and emotional loneliness. Results: Although social loneliness was not associated with mortality in those living alone, emotional loneliness was; with each 1 SD increase in emotional loneliness, there was an 18.6% increased risk of all-cause mortality in the fully adjusted model ( HR = 1.186, p = .029). No associations emerged for social or emotional loneliness among those not living alone. Examinations of potential moderators revealed that with each 1 SD increase in functional status, the risk associated with emotional loneliness for all-cause mortality increased by 17.9% (hazard ratiointeraction = 1.179, p = .005) in those living alone. No interaction between personality traits with loneliness emerged. Conclusions: Emotional loneliness is associated with an increased risk of all-cause mortality in older adults who live alone. Functional status was identified as one potential pathway accounting for the adverse consequences of loneliness. Emotional loneliness that can arise out of the loss or absence of a close emotional attachment figure seems to be the toxic component of loneliness.